Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas V SD Gmim 24 Manembo-Nembo di Kota Bitung - Ruung, Yulianita; Paus, Julduz Ruland; Sumilat, Margareta (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this research is to determine and improve student learning outcomes in social studies subjects for class V at SD GMIM 24 Manembo-Nembo after implementing the Problem Based Learning (PBL) learning model. In this research, researchers used the Classroom Action Education (CAE) research method. Data collection was carried out by means of observation and tests in cycle 1, cycle 2 which were carried out directly in class 5. The results in cycle I obtained student learning outcomes with a percentage of 61.6% of the total of 30 students, only 9 people were successful and 21 students were not. succeed. Thus, after correcting the deficiencies in cycle I, research in cycle II obtained learning results from a total of 30 students, of which 27 students were successful and only 3 students were unsuccessful with a percentage of 81.3% or can be said to be successful based on the research results and discussion in class V GMIM 24 Manembo-Nembo, it can be concluded that; Application of the Problem Based Learning (PBL) Learning Model to Improve Student Learning Outcomes in Class V Social Sciences Subjects at GMIM 24 Manembo-Nembo Elementary School in Bitung City with an achievement in cycle I of 61.6% and cycle II of 81.3%. Based on research that has been conducted in class V of SD GMIM 24 Manembo-Nembo, it can be concluded that the application of the Problem Based Learning (PBL) learning model can improve social studies learning outcomes in the Geographical Location of Indonesia material with the Problem Based Learning (PBL) learning model helping students be more active in learning process.